Dinamika Komunikasi Interpersonal dan Keharmonisan Keluarga: Tinjauan Sistematis Berbasis PRISMA - Firyal Grahita Monica; Teguh Dwi Putranto (MUKASI: Jurnal Ilmu Komunikasi, 2025)
Interpersonal communication has an important role in shaping and maintaining harmonious relationships between children and parents in the family. as social beings we need to communicate. In the context of family, interpersonal communication is not only a means of conveying messages, but as a foundation for forming emotional bonds. This study aims to understand in depth how interpersonal communication contributes to the harmonious relationship between children and parents, as well as how social challenges affect these dynamics. This research uses the literature review method with the PRISMA model. The literature search was conducted with documentation. Documentation was conducted through the Google Scholar database with keywords used including interpersonal communication and family relationships, interpersonal communication and parents and children, communication in the family and emotional closeness. The search process was limited to publications between 2024 and 2025 to ensure compatibility with recent research developments in the field of family communication. At the identification stage, the search yielded nine articles. This study found that healthy interpersonal communication characterized by openness, empathy, and consistent emotional presence can improve children's emotional attachment and ability to establish social relationships. Conversely, communication barriers can lead to misunderstandings, emotional distance, and conflict between family members. Therefore, strengthening adaptive and responsive interpersonal communication patterns is the key to building a harmonious family in the midst of the dynamics of the times.